Polymer microsphere for cable sheath material and preparation method thereof
By introducing functional crosslinking agents into the wall material of polymer microspheres, a three-dimensional crosslinking network structure is formed, the problem of insufficient heat resistance and waterproofing properties of acrylic resin is solved, and the multifunctional performance of polymer microspheres is improved, which is suitable for cable sheath materials.
Patent Information
- Application Number
- CN202411920222.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-18
AI Technical Summary
In the prior art, the heat resistance and waterproofing properties of acrylic resin as polymer microsphere raw materials have poor heat resistance and waterproofing properties, resulting in a significant reduction in performance under long-term water erosion and thermal aging, which cannot meet the higher demand for cable sheath materials.
By introducing functional crosslinking agents into the wall material of polymer microspheres, a more complete three-dimensional crosslinking network structure is formed, which improves the heat resistance and water resistance of polymer microspheres, and gives them antistatic, anti-aging and antibacterial properties.
It has achieved improved heat resistance and water resistance of polymer microspheres, reduced cable weight, and improved antistatic, anti-aging and antibacterial properties, and is suitable for cable sheathing materials.
Smart Images

Figure BDA0005207784830000041 
Figure BDA0005207784830000051 
Figure BDA0005207784830000052
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer microspheres, and in particular relates to polymer microspheres used for cable sheath materials and a preparation method thereof. Background Art
[0002] With the rapid development of the economy, the use and density of cables are increasing. Power cables are as indispensable to modern life as the arteries of the human body. For cables, in addition to metal cores, other structural materials are: outer sheath materials (polyethylene, polyvinyl chloride or modified rubber), fillers (polyethylene, polypropylene, polyvinyl chloride or vaseline, etc.) and refractory mud, glass fiber rope, metal shielding layer and other materials coated therein. Among these structural auxiliary materials, outer sheath materials and fillers account for a large part of the weight. Therefore, the improvement of cable lightweight performance mainly depends on outer sheath materials and fillers.
[0003] Filling microspheres are a new type of spherical special filling material, the main component of which is organic high molecular polymer, with a diameter of 10-50 microns and low boiling point hydrocarbons. When the microspheres are heated to a certain temperature, the thermoplastic shell softens, and the low boiling point hydrocarbons inside the shell expand, so that the volume can be increased to dozens of times its own, while the core-shell structure is not destroyed, thereby achieving the effect of expansion. During expansion, the pressure generated by the core material is balanced with the tension generated by the resin wall material due to stretching. Within a certain temperature range, the higher the temperature, the greater the pressure generated by the core material, and the resin wall material will continue to stretch in order to balance this pressure, so that the microspheres continue to expand and maintain the balloon shape (stable bubble) at a certain temperature. Even when the temperature drops, the microspheres can still maintain their original state due to the cooling and hardening of the shell. Polymer microspheres are different from other fillers. They have no pores themselves, will not break or rebound. At the same time, the ball wall is an organic polymer material, and has certain toughness and wear resistance. The addition of materials for filling microspheres can well enhance the mechanical and physical properties of the substrate. Filling microspheres are very light and can significantly reduce the specific gravity of the substrate. In addition, the filled microspheres also have the advantages of being easy to process, environmentally friendly and non-toxic, etc. However, there are few prior arts that use polymer microspheres as additives to reduce cable quality and improve cable performance.
[0004] Commonly used high molecular polymer matrices for polymer microspheres include acrylic resin, phenolic resin, styrene and vinyl chloride copolymers, etc. Among them, acrylic resin is inexpensive, has little environmental pollution and good performance, and is an ideal raw material for high molecular polymer microspheres. However, acrylic resin has poor heat resistance and waterproof properties. Under long-term water erosion and thermal aging, the performance of acrylic resin will be greatly reduced. Therefore, it is urgent to improve the above defects to meet higher demands in the technical field. Summary of the invention
[0005] The object of the present invention is to provide a polymer microsphere for cable sheath material and a preparation method thereof, so as to overcome the above-mentioned defects of the prior art.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] A method for preparing polymer microspheres for cable sheath materials comprises the following steps:
[0008] The first step is to mix and stir polyvinyl alcohol, sodium chloride, sodium nitrite aqueous solution (mass fraction 1%), hydrazine hydrate aqueous solution (mass fraction 1%) and deionized water in a mixing and stirring tank to obtain an aqueous phase composition;
[0009] Step 2: acrylonitrile, methyl methacrylate, styrene, methacrylic acid and a crosslinking agent are mixed, and then an inert hydrocarbon foaming agent and an initiator are added and mixed to obtain an oil phase composition;
[0010] The third step is to put the aqueous phase composition, the oil phase composition and the emulsifier into a homogenizer, homogenize for 30-40 minutes at a speed of 2000-10000 rpm, and then put them into a polymerization kettle, replace with nitrogen, and maintain the pressure at 0.15-2MPa. Slowly raise the temperature to 45°C-75°C to start the reaction, react for 10-12 hours under uniform stirring, filter, wash the filter cake with deionized water, dry in an oven, and crush to obtain polymer microspheres.
[0011] Furthermore, the inert hydrocarbon foaming agent is any one of isopentane, isooctane and n-octane.
[0012] Furthermore, the initiator is 2,2'-azobisisobutyronitrile or di-(2-ethylhexyl) peroxydicarbonate.
[0013] Furthermore, the emulsifier is one of alkylphenol polyoxyethylene ether and sodium lauryl sulfate.
[0014] Furthermore, the above raw materials are calculated in parts by weight as follows: 0.05-0.07 parts of polyvinyl alcohol, 0.5-0.7 parts of sodium chloride, 5-8 parts of sodium nitrite aqueous solution, 4-6 parts of hydrazine hydrate aqueous solution, 20-30 parts of deionized water, 60-80 parts of acrylonitrile, 20-30 parts of methyl methacrylate, 8-12 parts of styrene, 10-15 parts of methacrylic acid, 2-3 parts of crosslinking agent, 10-14 parts of inert hydrocarbon foaming agent, 0.8-1 parts of initiator, and 2-3 parts of emulsifier.
[0015] Furthermore, the cross-linking agent is prepared by the following steps:
[0016] S1. Add ethylenediamine, triethylamine, acetone and hexane to a three-necked flask equipped with a stirring device and a condensing device, stir and dissolve evenly, place the flask in an ice-water bath, control the system temperature not to exceed 2°C, then slowly drop 6-chloro-1-hexene, remove the ice bath after the addition is complete, react at room temperature for 2h, filter (remove the generated salt), take the organic phase (liquid phase), wash it 4-5 times with a 20% mass fraction NaCl aqueous solution, anhydrous Mg 2 SO 4 Dry, filter, and finally distill under reduced pressure to remove the solvent (hexane) to obtain intermediate product 1;
[0017] The ratio of ethylenediamine, triethylamine and 6-chloro-1-hexene is 6.1-6.5 g:10.1 g:11.8 g;
[0018] Under the action of triethylamine, the -NH 2 A nucleophilic substitution reaction occurs with the chlorine group on the 6-chloro-1-hexene molecule. By controlling the molar ratio of the two to be close to 1:1 and a slight excess of ethylenediamine, a substitution reaction occurs to obtain the intermediate product 1. The reaction process is shown below:
[0019]
[0020] S2. Add 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid, triethylamine (acid binding agent) and anhydrous dichloromethane to a three-necked flask equipped with a stirring device and a condensing reflux device, introduce nitrogen gas for 10 min, then add intermediate 1 and DIC (N,N-diisopropylcarbodiimide, dehydrating agent), and heat at room temperature and N 2 The mixture was stirred and reacted for 3 h under protection. After the reaction, it was extracted three times with hot distilled water (temperature 60-70°C). The organic layer was taken, dried over anhydrous magnesium sulfate, filtered, and rotary evaporated to obtain intermediate 2.
[0021] The ratio of 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid, triethylamine, intermediate 1, and DIC is 27.8 g: 10.1 g: 14-16 g: 12.6 g;
[0022] Under the action of triethylamine and DIC, the -COOH on the 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid molecule and the -NH on the 2,6-diaminopyridine molecule 2 An amidation reaction occurs to obtain the intermediate product 2. The reaction process is as follows:
[0023]
[0024] S3, use N 2The air in the four-necked flask was removed, and then the intermediate product 2 and DMF (N,N-dimethylformamide) were added and stirred to mix evenly. The temperature in the flask was controlled at 35-40°C, and a mixture of cyanuric chloride, triethylamine and DMF was slowly dripped in under stirring. After the addition was completed, the reaction was continued at 40°C for 4 hours. After the reaction was completed, it was naturally cooled to room temperature, a large amount of deionized water was added, and organic matter was precipitated. Finally, the obtained organic matter was dried to obtain the intermediate product 3;
[0025] The ratio of the amount of intermediate product 2, cyanuric chloride and triethylamine is 36.5-40g:5.5g:9.1g;
[0026] Under the action of triethylamine, -NH- on the intermediate product 2 molecule undergoes a nucleophilic substitution reaction with -Cl on the cyanuric chloride molecule to obtain the intermediate product 3. The reaction process is as follows:
[0027]
[0028] S4, after mixing the intermediate product 3 with tetrahydrofuran, adding iodomethane, stirring and reacting at room temperature for 16 hours, after the reaction is completed, removing tetrahydrofuran and excess iodomethane by rotary evaporation to obtain a cross-linking agent;
[0029] The ratio of the intermediate product 3 to methyl iodide is 12g:20-30g;
[0030] The tertiary N on the intermediate product 3 molecule undergoes a quaternization reaction under the action of methyl iodide to form N positive ions to obtain a cross-linking agent. The structural formula of the cross-linking agent is shown below:
[0031]
[0032] From the molecular structure point of view, the obtained cross-linking agent has a s-triazine ring at the center, and three carbon chains are distributed in a dendrite-like manner around the s-triazine ring, and the end of the carbon chain is an unsaturated C=C. Under the action of an initiator, the end of the branched carbon chain of the cross-linking agent can undergo chemical cross-linking with monomers such as acrylonitrile and methyl methacrylate, thereby forming a cross-linked three-dimensional network structure, which constitutes the shell part of the polymer microsphere. The cross-linked network structure can not only improve the mechanical properties of the polymer microsphere, but also improve its expansion and heat resistance. In addition, the cross-linking agent also contains N positive ions, which are introduced into the polymer microspheres, so that the polymer microspheres have certain antistatic properties and are used in cable sheath materials. When used in cable sheath materials, it can improve the electrostatic effect on the cable surface; the triazine ring in the center of the crosslinking agent also has certain antibacterial properties, and works together with N positive ions (quaternary ammonium salt antibacterial mechanism) to give the polymer microspheres certain antibacterial properties, which can not only prolong the shelf life, but also give the cable certain antibacterial and corrosion resistance when used in cable sheath materials; the crosslinking agent molecule also contains multiple hindered phenol structures, which is a highly efficient and safe anti-aging agent, so that the polymer microspheres have good anti-aging properties. When used in cable sheath materials, it can synergize with other anti-ultraviolet and anti-aging components in the material, thereby greatly improving the anti-aging performance of the cable;
[0033] It should be noted that the cross-linking agent is combined with the shell of the microspheres in the form of multiple chemical bonds, and the polymer microspheres can produce chemical reactions with the protective cover material matrix. Therefore, the effective ingredients on the cross-linking agent are not easy to migrate and seep out, ensuring the long-term stability of the performance.
[0034] Another object of the present invention is to provide a polymer microsphere prepared by the above preparation method, and the polymer microsphere can be applied to cable sheath materials.
[0035] Beneficial effects of the present invention:
[0036] The polymer microspheres of the present invention use monomers such as acrylonitrile, methyl methacrylate, acrylic acid, etc. as wall layer raw materials to obtain polyacrylate polymer microspheres, which have the advantages of low price, little environmental pollution, and good performance;
[0037] The present invention introduces a functional cross-linking agent into the wall layer material, which not only enables the wall layer to form a more complete three-dimensional cross-linked network structure and improves the heat resistance and water resistance of the polymer microspheres, but also can give the polymer microspheres certain antistatic and anti-aging functional properties. When the polymer microspheres are applied to cable sheath materials, they can not only reduce the weight of the cable, but also improve the antistatic and anti-aging properties of the cable, and have very important application value. DETAILED DESCRIPTION
[0038] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] Embodiment 1
[0040] Prepare the cross-linking agent:
[0041] S1. Add 6.1 g of ethylenediamine, 10.1 g of triethylamine, 30 mL of acetone and 50 mL of hexane into a three-necked flask equipped with a stirring device and a condensing device, stir and dissolve evenly, place the flask in an ice-water bath, control the system temperature not to exceed 2°C, then slowly drop 11.8 g of 6-chloro-1-hexene, remove the ice bath after the addition is complete, react at room temperature for 2 h, filter (remove the generated salt), take the organic phase (liquid phase), wash 4 times with a 20% mass fraction of NaCl aqueous solution, anhydrous Mg 2 SO 4 Dry, filter, and finally distill under reduced pressure to remove the solvent (hexane) to obtain intermediate product 1;
[0042] S2. Add 27.8 g of 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid, 10.1 g of triethylamine (acid binding agent) and 100 mL of anhydrous dichloromethane to a three-necked flask equipped with a stirring device and a condensing reflux device, introduce nitrogen, and continue to introduce nitrogen for 10 min. Then, add 14 g of intermediate product 1 and 12.6 g of DIC, and continue to stir at room temperature and N 2 The reaction was stirred for 3 h under protection. After the reaction was completed, it was extracted three times with hot distilled water (temperature 60°C). The organic layer was taken, dried over anhydrous magnesium sulfate, filtered, and rotary evaporated to obtain intermediate product 2.
[0043] S3, use N 2 The air in the four-necked flask was removed, and 36.5 g of the intermediate product 2 and 80 mL of DMF were added, and the mixture was stirred and mixed evenly. The temperature in the flask was controlled to be 35°C, and a mixture of 5.5 g of cyanuric chloride, 9.1 g of triethylamine and 35 mL of DMF was slowly added dropwise under stirring. After the addition was completed, the reaction was continued at 40°C for 4 h. After the reaction was completed, it was naturally cooled to room temperature, a large amount of deionized water was added, and the organic matter was precipitated. Finally, the obtained organic matter was dried to obtain the intermediate product 3;
[0044] S4. After mixing 12 g of the intermediate product 3 with 50 mL of tetrahydrofuran, 20 g of methyl iodide was added, and the mixture was stirred and reacted at room temperature for 16 h. After the reaction was completed, tetrahydrofuran and excess methyl iodide were removed by rotary evaporation to obtain a cross-linking agent.
[0045] Embodiment 2
[0046] Prepare the cross-linking agent:
[0047] S1. Add 6.5 g of ethylenediamine, 10.1 g of triethylamine, 30 mL of acetone and 50 mL of hexane to a three-necked flask equipped with a stirring device and a condensing device, stir and dissolve evenly, place the flask in an ice-water bath, control the system temperature not to exceed 2°C, then slowly drop 11.8 g of 6-chloro-1-hexene, remove the ice bath after the addition is complete, react at room temperature for 2 h, filter (remove the generated salt), take the organic phase (liquid phase), wash 5 times with a 20% mass fraction of NaCl aqueous solution, anhydrous Mg 2 SO 4 Dry, filter, and finally distill under reduced pressure to remove the solvent (hexane) to obtain intermediate product 1;
[0048] S2. Add 27.8 g of 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid, 10.1 g of triethylamine (acid binding agent) and 100 mL of anhydrous dichloromethane to a three-necked flask equipped with a stirring device and a condensing reflux device, introduce nitrogen, and continue to introduce nitrogen for 10 min. Then, add 16 g of intermediate 1 and 12.6 g of DIC, and continue to stir at room temperature and N 2 The mixture was stirred and reacted for 3 h under protection. After the reaction was completed, it was extracted three times with hot distilled water (temperature 70°C). The organic layer was taken, dried over anhydrous magnesium sulfate, filtered, and rotary evaporated to obtain intermediate product 2.
[0049] S3, use N 2 The air in the four-necked flask was removed, and 40 g of the intermediate product 2 and 80 mL of DMF were added, and the mixture was stirred and mixed evenly. The temperature in the flask was controlled at 40°C, and a mixture of 5.5 g of cyanuric chloride, 9.1 g of triethylamine and 35 mL of DMF was slowly dropped under stirring. After the addition was completed, the reaction was continued at 40°C for 4 h. After the reaction was completed, it was naturally cooled to room temperature, a large amount of deionized water was added, and the organic matter was precipitated. Finally, the obtained organic matter was dried to obtain the intermediate product 3;
[0050] S4. After mixing 12 g of the intermediate product 3 with 50 mL of tetrahydrofuran, 30 g of methyl iodide was added, and the mixture was stirred and reacted at room temperature for 16 h. After the reaction was completed, tetrahydrofuran and excess methyl iodide were removed by rotary evaporation to obtain a cross-linking agent.
[0051] Embodiment 3
[0052] A method for preparing polymer microspheres for cable sheath materials comprises the following steps:
[0053] Step 1: In a mixing and stirring tank, 0.05 parts of polyvinyl alcohol, 0.5 parts of sodium chloride, 5 parts of sodium nitrite aqueous solution (mass fraction 1%), 4 parts of hydrazine hydrate aqueous solution (mass fraction 1%) and 20 parts of deionized water are mixed and stirred uniformly to obtain an aqueous phase composition;
[0054] Step 2: 60 parts of acrylonitrile, 20 parts of methyl methacrylate, 8 parts of styrene, 10 parts of methacrylic acid, and 2 parts of the crosslinking agent prepared in Example 1 are mixed, and then 10 parts of isopentane and 0.8 parts of 2,2'-azobisisobutyronitrile are added and mixed to obtain an oil phase composition;
[0055] The third step is to put the aqueous phase composition, the oil phase composition and 2 parts of alkylphenol polyoxyethylene ether into a homogenizer, homogenize for 40 minutes at a speed of 2000 rpm, and then put them into a polymerization kettle, replace with nitrogen, and maintain the pressure at 0.15 MPa. Slowly raise the temperature to 45°C to start the reaction. Under uniform stirring, react for 12 hours, filter, wash the filter cake with deionized water, dry in an oven, and crush to obtain polymer microspheres.
[0056] Embodiment 4
[0057] A method for preparing polymer microspheres for cable sheath materials comprises the following steps:
[0058] Step 1: In a mixing and stirring tank, 0.06 parts of polyvinyl alcohol, 0.6 parts of sodium chloride, 6.5 parts of sodium nitrite aqueous solution (mass fraction 1%), 5 parts of hydrazine hydrate aqueous solution (mass fraction 1%) and 25 parts of deionized water are mixed and stirred uniformly to obtain an aqueous phase composition;
[0059] Step 2: 70 parts of acrylonitrile, 25 parts of methyl methacrylate, 10 parts of styrene, 12.5 parts of methacrylic acid, and 2.5 parts of the crosslinking agent prepared in Example 1 were mixed, and then 12 parts of isooctane and 0.9 parts of di-(2-ethylhexyl) peroxydicarbonate were added and mixed to obtain an oil phase composition;
[0060] The third step is to put the aqueous phase composition, the oil phase composition and 2.5 parts of sodium dodecyl sulfate into a homogenizer, homogenize at a speed of 6000 rpm for 35 minutes, and then put into a polymerization kettle, replace with nitrogen, and maintain the pressure at 0.18 MPa. Slowly raise the temperature to 60°C to start the reaction. Under uniform stirring, react for 11 hours, filter, wash the filter cake with deionized water, dry in an oven, and crush to obtain polymer microspheres.
[0061] Embodiment 5
[0062] A method for preparing polymer microspheres for cable sheath materials comprises the following steps:
[0063] Step 1: In a mixing and stirring tank, 0.07 parts of polyvinyl alcohol, 0.7 parts of sodium chloride, 8 parts of sodium nitrite aqueous solution (mass fraction 1%), 6 parts of hydrazine hydrate aqueous solution (mass fraction 1%) and 30 parts of deionized water are mixed and stirred uniformly to obtain an aqueous phase composition;
[0064] Step 2: 80 parts of acrylonitrile, 30 parts of methyl methacrylate, 12 parts of styrene, 15 parts of methacrylic acid, and 3 parts of the crosslinking agent prepared in Example 1 were mixed, and then 14 parts of n-octane and 1 part of di-(2-ethylhexyl) peroxydicarbonate were added and mixed to obtain an oil phase composition;
[0065] The third step is to put the aqueous phase composition, the oil phase composition and 3 parts of alkylphenol polyoxyethylene ether into a homogenizer, homogenize for 30 minutes at a speed of 10,000 rpm, and then put them into a polymerization kettle, replace with nitrogen, and maintain the pressure at 2 MPa. Slowly raise the temperature to 75°C to start the reaction. Under uniform stirring, react for 10 hours, filter, wash the filter cake with deionized water, dry in an oven, and crush to obtain polymer microspheres.
[0066] Comparative Example 1
[0067] The polymer microspheres are obtained by replacing the cross-linking agent in Example 3 with ethylene glycol dimethacrylate and keeping the other raw materials and the preparation process unchanged.
[0068] 100 hollow polymer microspheres prepared in Examples 3 to 5 were randomly selected to test the sphericity and observe whether cracks were generated, and the yield of microspheres with a sphericity higher than 99.9% and the probability of cracked microspheres were obtained; in addition, the time during which the microspheres did not turn yellow or crack under the condition of 220° C. was tested; the test results are shown in Table 1 below:
[0069] Table 1
[0070]
[0071]
[0072] It can be seen from the data in Table 1 above that the polymer microspheres obtained by the present invention have good shape and heat resistance; combined with the data of Comparative Example 1, it can be seen that the crosslinking agent of the present invention can promote the microspheres to form a more complete three-dimensional network structure, thereby improving the mechanical properties and heat resistance.
[0073] The polymer microspheres obtained in Examples 3 to 5 and Comparative Example 1 were applied to the cable sheath material, and the specific process was as follows:
[0074] 80g of polyvinyl chloride resin, 12g of polyethylene resin, 10g of expanded microspheres and 4g of paraffin (lubricant) are added to a high-speed mixer in sequence for mixing. After mixing evenly, they are transferred to a twin-screw plasticator for plasticizing. After plasticizing evenly, they are drawn into strips through water cooling and pelletized. After drying in a centrifugal dryer, cable sheath material is obtained.
[0075] The following performance tests are conducted on the above cable sheath materials:
[0076] GB / T 19466.6-2009 was used to measure the induction time of the sample before and after hot air oxidation at 150°C for 48 hours.
[0077] GB / T 1040.2-2006 was used to measure the tensile properties of the samples, and then the tensile strength of the samples after the test in the heat aging test chamber was tested. The test temperature was 120°C and the test time was 48 hours. The tensile strength retention rate was calculated using the formula [tensile strength after aging / tensile strength before aging × 100%] to evaluate the aging resistance.
[0078] The surface resistivity of the test sample was tested using GB / T 1410-2006;
[0079] The measured results are shown in Table 2 below:
[0080] Table 2
[0081]
[0082] It can be seen from the data in Table 2 above that when the polymer microspheres obtained in the present invention are applied to the sheath layer material of the cable, the anti-aging and antistatic properties of the sheath layer can be effectively improved.
[0083] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing polymer microspheres for cable sheath materials, characterized in that: The following steps are involved: The first step is to mix and stir polyvinyl alcohol, sodium chloride, sodium nitrite aqueous solution, hydrazine hydrate aqueous solution and deionized water in a mixing and stirring tank to obtain an aqueous phase composition; Step 2: acrylonitrile, methyl methacrylate, styrene, methacrylic acid and a crosslinking agent are mixed, and then an inert hydrocarbon foaming agent and an initiator are added and mixed to obtain an oil phase composition; The third step is to put the aqueous phase composition, the oil phase composition and the emulsifier into a homogenizer, homogenize for 30-40 minutes at a speed of 2000-10000 rpm, and then put them into a polymerization kettle, replace with nitrogen, and maintain the pressure at 0.15-2MPa. Slowly raise the temperature to 45°C-75°C to start the reaction, react for 10-12 hours under uniform stirring, filter, wash the filter cake with deionized water, dry in an oven, and crush to obtain polymer microspheres.
2. The method for preparing polymer microspheres for cable sheath materials according to claim 1, characterized in that: The inert hydrocarbon foaming agent is any one of isopentane, isooctane and n-octane.
3. The method for preparing polymer microspheres for cable sheath materials according to claim 1, characterized in that: The initiator is 2,2'-azobisisobutyronitrile or di-(2-ethylhexyl) peroxydicarbonate.
4. The method for preparing polymer microspheres for cable sheath materials according to claim 1, characterized in that: The emulsifier is one of alkylphenol polyoxyethylene ether and sodium lauryl sulfate.
5. The method for preparing polymer microspheres for cable sheath materials according to claim 1, characterized in that: The above raw materials are calculated in parts by weight as follows: 0.05-0.07 parts of polyvinyl alcohol, 0.5-0.7 parts of sodium chloride, 5-8 parts of sodium nitrite aqueous solution, 4-6 parts of hydrazine hydrate aqueous solution, 20-30 parts of deionized water, 60-80 parts of acrylonitrile, 20-30 parts of methyl methacrylate, 8-12 parts of styrene, 10-15 parts of methacrylic acid, 2-3 parts of crosslinking agent, 10-14 parts of inert hydrocarbon foaming agent, 0.8-1 parts of initiator, and 2-3 parts of emulsifier.
6. The method for preparing polymer microspheres for cable sheath materials according to claim 1, characterized in that: The cross-linking agent is prepared by the following steps: S1. Add ethylenediamine, triethylamine, acetone and hexane into a three-necked flask, stir and dissolve evenly, and place the flask in an ice-water bath, control the system temperature not to exceed 2°C, and then slowly drop 6-chloro-1-hexene. After the dropwise addition is completed, remove the ice bath and react at room temperature for 2 hours to obtain intermediate 1; S2. Add 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid, triethylamine and anhydrous dichloromethane into a three-necked flask, introduce nitrogen for 10 min, then add intermediate 1 and DIC, and stir the mixture at room temperature under N2 protection for 3 h to obtain intermediate 2. S3, remove the air in the four-necked flask with N2, add the intermediate product 2 and DMF, stir and mix evenly, control the temperature to 35-40°C, slowly drop the mixture of cyanuric chloride, triethylamine and DMF under stirring, continue to react at 40°C for 4h after the addition is complete, and obtain the intermediate product 3; S4. After mixing the intermediate product 3 with tetrahydrofuran, iodomethane was added, and the mixture was stirred at room temperature for 16 hours. After the reaction was completed, tetrahydrofuran and excess iodomethane were removed by rotary evaporation to obtain a cross-linking agent.
7. The method for preparing polymer microspheres for cable sheath materials according to claim 6, characterized in that: In step S1, the ratio of ethylenediamine, triethylamine and 6-chloro-1-hexene is 6.1-6.5 g:10.1 g:11.8 g.
8. The method for preparing polymer microspheres for cable sheath materials according to claim 6, characterized in that: In step S2, the ratio of the amount of 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid, triethylamine, intermediate 1, and DIC is 27.8 g: 10.1 g: 14-16 g: 12.6 g.
9. The method for preparing polymer microspheres for cable sheath materials according to claim 6, characterized in that: In step S3, the ratio of the amount of the intermediate product 2, cyanuric chloride and triethylamine is 36.5-40g:5.5g:9.1g.
10. A polymer microsphere for cable sheath material, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 9.